Raspberry-like CuWO4 hollow spheres anchored on sulfur-doped g-C3N4 composite: An efficient electrocatalyst for selective electrochemical detection of antibiotic drug nitrofurazone. (June 2022) - Anupriya, Jeyaraman; Rajakumaran, Ramachandran; Chen, Shen Ming; Karthik, Raj; Kumar, Jeyaraj Vinoth; Shim, Jae-Jin; Shafi, P. Muhammed; Lee, Jeong-Won
Abstract: We report a highly selective and sensitive electrochemical sensor for the determination of nitrofurazone (NZ) based on sulfur-doped graphitic carbon nitride with copper tungstate hollow spheres (Sg–C3 N4 /CuWO4 ). Here, a Sg–C3 N4 /CuWO4 composite was synthesized by a facile ultrasonic method. The physicochemical properties of the composite were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), energy dispersive X-ray spectroscopy (EDX) and X-ray photoelectron spectroscopy (XPS). Then, the surface morphology of the composite material was investigated by field emission scanning electron microscopy (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM). Moreover, the electrochemical activity of the as-synthesized composite material was initially tested using electrochemical impedance spectroscopy (EIS). The electroanalytical techniques namely cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were carried out for the electrochemical studies. The proposed sensor exhibits lower LOD and good sensitivity of about 3 nM and 1.24 μAμM −1 cm −2 to NZ detection. In addition, the Sg–C3 N4 /CuWO4 modified electrode showed excellent repeatability, reproducibility, long-term storage stability and excellent selectivity. The developed sensor was successfully applied for the determination of NZ in human urine and serum samples and achieved good recovery results. Graphical abstract: Image 1 Highlights: The selective electrochemical sensor was proposed for NZ detection. For the first time, Sg–C3 N4 /CuWO4 was prepared by facile ultrasonication method. The Sg–C3 N4 /CuWO4 fabricated GCE displayed good electrochemical activity. The designed electrode owns a LOD (3 nM) and sensitivity (1.24 μAμM −1 cm −2 ). We obtained good recovery results for real sample analysis in biological samples.